Analisis Reduplikasi Pada Cerpen Guru karya Putu Wijaya - Muhammad Arifin; Mimin Trianjani; Zulfa Sofiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the use of reduplication in the short story